2015
DOI: 10.2147/ijgm.s84537
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in Sub-Saharan Africa: epidemiology, unmet needs, and treatment options

Abstract: Health care in Sub-Saharan Africa is being challenged by a double burden of disease as lifestyle diseases common in the developed world, such as stroke and atrial fibrillation (AF), increase, while, simultaneously, health issues of the developing world in terms of communicable disease persist. The prevalence of AF is lower in Africa than in the developed world but is expected to increase significantly over the next few decades. Patients with AF in Africa tend to be younger and have a higher prevalence of rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 67 publications
2
54
0
3
Order By: Relevance
“…A review published 4 years ago suggested that there is a dearth of information on the epidemiology of AF in SSA . However, this review was not systematic and did not capture much relevant data.…”
Section: Introductionmentioning
confidence: 99%
“…A review published 4 years ago suggested that there is a dearth of information on the epidemiology of AF in SSA . However, this review was not systematic and did not capture much relevant data.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, use of oral anticoagulants and not antiplatelets is the recommended treatment for AF in patients at high-risk of stroke, such as those with CHADS 2 scores of 2 or more, according to American Heart Association/European Society of Cardiology guidelines. [9] Considering that stroke related to AF is more disabling and carries greater risks of death and disability,[1516] our findings suggest the need for improved efforts at early detection and appropriate management of AF at primary care settings in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…The pulse rates here (result not shown) ranged from 72 to 100/minute; and none was reported as irregular. Atrial fibrillation is not common in African populations, either native on the continent or in the America [19]. There must be a genetic angle to it as African Americans are less encumbered than white Americans [20].…”
Section: Discussionmentioning
confidence: 99%